Signal-Adaptive Switching of Overlap Ratio in Audio Transform Coding - Helmrich, Christian; Edler, Bernd (2016 IEEE International Conference on Acoustics, Speech and Signal Processing (ICASSP), 2016)
Contemporary perceptual audio coders, all of which apply the modified discrete cosine transform (MDCT), with an overlap ratio of 50%, for frequency-domain quantization, provide good coding quality even at low bit-rates. However, relatively long frames are required for acceptable low-rate performance also for quasi-stationary harmonic input, leading to increased algorithmic latency and reduced temporal coding resolution. This paper investigates the alternative approach of employing the extended lapped transform (ELT), with 75% overlap ratio, on such input. To maintain a high time resolution for coding of transient segments, the ELT definition is modified such that frame-wise switching between ELT (for quasi-stationary) and MDCT coding (for non-stationary or non-tonal regions), with complete time-domain aliasing cancelation and no increase in frame length, becomes possible. A new ELT window function with improved side-lobe rejection to avoid framing artifacts is also derived. Blind subjective evaluation of the switched-ratio proposal confirms the benefit of the signal-adaptive design.<br